Conservation of Critical Elements of the Periodic Table. Issue 2 (2nd January 2019) - Supanchaiyamat, Nontipa; Hunt, Andrew J.
Abstract: Since its conception, the periodic table and the elements contained within it have shaped our modern lives. The use of many elements is now ubiquitous and essential for the modern technologies we have now become accustomed to. However, our use of some elements may be considered as unsustainable and their current use may create both economic and environmental pressures. The United Nations have designated 2019 the "International Year of the Periodic Table". As such this Essay presents some important points on "critical elements" and the importance of adopting sustainable practices in the use of all elements of the periodic table. This article also highlights a number of examples of green technologies for elemental recovery and some of the challenges we must overcome to become truly sustainable across the whole periodic table. Abstract : Save the elements : The periodic table of elements plays an important role in our modern lives as many elements are now ubiquitous and essential for the modern technologies. However, the use of some critical elements may be considered as unsustainable and their current use may create both economic and environmental pressures. For sustainable future economics, sustainable practices have to be adopted for the use and recovery of all elements in the periodic table.